PROXIMAL EXERCISES ARE EFFECTIVE IN TREATING PATELLOFEMORAL PAIN SYNDROME: A SYSTEMATIC REVIEW - Peters, Jeroen S.J. (Sports Physical Therapy Section, 2013)
BACKGROUND: Patellofemoral pain syndrome is a common disorder of the knee with multifactorial aetiology. Multimodal treatment, including exercise therapy, has been shown to be effective in the treatment of patellofemoral pain, although some patients continue to experience pain and dysfunction despite treatment. To address this, recent research has started to investigate the lumbo‐pelvic and hip girdle in patellofemoral pain. PURPOSE: The aim of this systematic review was to investigate the effectiveness of proximal exercises, compared with knee exercises, for patients with patellofemoral pain, in improving pain and function. METHODS: A computer‐based search (population: patients with patellofemoral pain, intervention: proximal [hip or lumbo‐pelvic] exercises, comparator: knee exercises, outcome: self‐reported pain and/or functional questionnaire) was undertaken. Medline, Embase, CINAHL, SportsDiscus, Cochrane Library and PEDro were searched for studies published between January 2011 and January 2013. The included studies were appraised independently using the McMaster Critical Review Form for Quantitative Studies. Data was extracted for the exercise prescription and applicable outcome measures, and a descriptive analysis undertaken. RESULTS: Eight studies (three randomized controlled trials, one clinical controlled trial, three cohort studies and one case series) of moderate to high methodological quality met the inclusion criteria. Proximal exercise programs showed a consistent reduction of pain and function in the treatment of patellofemoral pain. Knee exercise programs had variable outcomes. CONCLUSION: Proximal interventions provide relief of pain and improved function in the short and long term and therefore physical therapists should consider using proximal interventions for treatment of patellofemoral pain. LEVEL OF EVIDENCE: 3a